INTEGRAL ASSESSMENT OF ECOLOGICAL WELL-BEING OF COMPLEX SYSTEMS AS A METHOD FOR EVALUATING ENVIRONMENTAL IMPACT (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In the context of increasing anthropogenic pressure on natural and nature-technical systems, the assessment of environmental impact requires a more qualitative systemic toolkit. The task of determining ecological well-being in the context of assessing a system's impact on nature and society is fundamental to fulfilling every person's right to live in an environment conducive to their health and well-being. The aim of this work is to obtain an integral assessment of this systemic property – to determine the comprehensive impact of a complex natural and nature-technical system on nature and society from the perspective of ecological well-being. To achieve such a systemic property, a method of summary indicators is applied, allowing the transformation of a set of criteria into a clearly defined integral indicator of the assessed property.
Keywords: environmental well-being; natural-technogenic system; emergency situation; Tsimlyansk reservoir